The 'alien' next door: Antarctica in South American fiction - Wainschenker, P; Elizabeth Leane (2019)
The representation of Antarctica in fiction has drawn the attention of an increasing number of scholars during recent years. However, analyses undertaken so far have foregrounded English-language texts produced by writers located in the Northern Hemisphere. In these texts, Antarctica is often seen as a remote, oppositional and alien space. This article challenges the Anglocentric view of Antarctic representation by examining the way the region is imagined in South American fiction. After surveying the small body of criticism that deals with Spanish-language texts set in Antarctica, we focus closely on three twentiethcentury short works written in South America. Our analysis demonstrates that these three texts challenge the image of Antarctic as an underworld, opposed to and cut off from the rest of the world. Rather, in Antarctic literary imaginings of Argentina and Chile, the Drake Passage bridges the gap between Tierra del Fuego and Antarctica, acting not as a barrier between two opposed regions, but connecting landscapes with shared features. Aware of the evident geopolitical connotations to this construction of South American/Antarctic relations, we show that in Antarctic fiction from Argentina and Chile geographic proximity does not necessarily play in favour of nationalist rhetoric. Surprisingly, it can be at the core of texts that naturalise Anglophone hegemony. Moreover, while the three stories evoke a geographic imaginary very different from that produced by many Anglophone texts, they do not present a unified vision. Further research is needed to probe whether the geographic imaginaries constructed in these three short texts can be traced in a wider range of South American texts set in Antarctica.